Resistência de união à microtração de sistemas adesivos “condiciona-e-lava” de dois passos: efeito de diferentes tratamentos da superfície dentinária condicionada - Neves, Tamíris Pereira Da Costa; Leandrin, Thais Piragine; Tonetto, Mateus Rodrigues; Andrade, Marcelo Ferrarezi; Campos, Edson Alves De (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractIntroduction The development of adhesive systems allow manufacturers to develop materials with increasingly simplified techniques, but that still would promote adequate resistance values of immediate union. It is suggested that some treatments of dentin surface can facilitate the process of accession.Objective To evaluate the effects of different treatments in conditioned flat dentin surface on bond strength to microtensile 2-step etch-and-rinse adhesive systems.Material and method Ninety-six human third molars were divided into twelve groups (n = 8) randomly according to the used adhesive system (GI: Single Bond 2 - 3M ESPE; GII: Prime & Bond 2.1 - Dentsply; GIII: Excite - Ivoclar Vivadent) and type of treatment of the conditioned dentin (a: water; b: water + chlorhexidine; c: ethanol; d: chlorhexidine + ethanol). All teeth were restored with Charisma color A2 (Heraeus – Kulzer, Germany) and subjected to mechanical testing microtensile (EMIC DL-2000). The statistical test performed was ANOVA 1 factor supplemented with Tukey test.Result GIIc groups GIIIc and GIId showed statistically significant increase in bond strength to immediate microtensile.Conclusion The different treatments of dentin did not affect negatively the bond strength for all tested adhesive systems and the use of the technique with ethanol, with or without chlorhexidine, appears to be an interesting approach when combined with 2-step etch-and-rinse adhesive systems.

ResumoIntrodução A evolução dos sistemas adesivos permitiu que os fabricantes desenvolvessem materiais com técnicas cada vez mais simplificadas, porém que, ainda assim, promovessem adequados valores de resistência de união imediata. Sugere-se que alguns tratamentos da superfície dentinária podem favorecer esse processo de adesão.Objetivo Avaliar os efeitos de diferentes tratamentos, em superfície dentinária plana condicionada, sobre a resistência de união à microtração de sistemas adesivos do tipo “condiciona-e-lava” de dois passos.Material e método Noventa e seis terceiros molares humanos foram divididos em 12 grupos (n=8), aleatoriamente, de acordo com o sistema adesivo utilizado (GI: Adper Single Bond 2 - 3M ESPE; GII: Prime & Bond 2.1 - Dentsply; GIII: Excite - Ivoclar Vivadent) e o tipo de tratamento do substrato dentinário condicionado (a: água; b: clorexidina + água; c: etanol; d: clorexidina + etanol). Todos os dentes foram restaurados com resina Charisma na cor A2 (Heraeus - Kulzer, Germany) e submetidos a ensaio mecânico de microtração (EMIC DL-2000). O teste estatístico realizado foi ANOVA a um fator, completado com teste de Tukey.Resultado Os grupos GIIc, GIIIc e GIId apresentaram aumento significativo estatisticamente na resistência de união à microtração imediata.Conclusão Os diferentes tratamentos da dentina condicionada não afetaram de maneira negativa a resistência de união para todos os sistemas adesivos testados e a utilização da técnica com etanol, associado ou não à clorexidina, parece ser uma interessante abordagem quando associada a sistemas adesivos “condiciona-e-lava” de dois passos.
Microtensile bond strength of 2-step etch-and-rinse adhesive systems: Effects of different treatments of etched dentin
Keywords: Adhesives; dentin; chlorhexidine; ethanol; bond strength; Adesivos dentinários; dentina; clorexidina; etanol; resistência de união